IMPLEMENTASI PERATURAN DAERAH NO. 5 TAHUN 2014 KOTA SEMARANG TENTANG PENANGANAN ANAK JALANAN, GELANDANGAN, DAN PENGEMIS - Arif Kurnia Ardi Pradana; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2017)
This research aimed to clarify the role of the Stakeholders involved in implementing the policy on the handling of street children, hemeless, and beggars in the city of Semarang and explained the driving factor and a barrier to the implementation effort handling of street children, the homeless and beggars in the City of Semarang. Research methods uses qualitative exploration, the approach data collection with techniques observation, interviews, and study of the document. Informants in this study is the social service of the Semarang City, the NGO Yayasan Emas Indonesia, former street children, as well as the community. Data were analyzed with the theory of "5 appropriate in the implementation of the policy" form Riant Nugroho and Van Meter Van Horn "policy implementation process model Van Meter Van Horn". The research results showed that the current goals expected by the Government in handling the street children, the homeless, and beggars have not achieved because the policy contained in the regulation of those areas have not been able to overcome the existing problems and there are still constraints in its implementation. Nevertheless, the Regulation of this area has grown to be carried out properly by the Social Service of the Semarang City as executor using a preventative approach & rehabilitation and assisted by Satpol PP as well as from Foundations/NGOs. A recommendation could be made to improve the performance of the implementation is the addition of the supporting resources implementation, sustainable empowerment, counseling, socialization, the number of logging, as well as the passage of the regulations the Mayor as a technical guide in the implementation.